2004
DOI: 10.1073/pnas.0405255101
|View full text |Cite
|
Sign up to set email alerts
|

Binding between the Niemann–Pick C1 protein and a photoactivatable cholesterol analog requires a functional sterol-sensing domain

Abstract: Niemann-Pick type C (NPC) 1 protein plays important roles inTreating cells with either U-18666A, a compound that creates an NPC-like phenotype, or with bafilomycin A1, a compound that raises late endosomal pH, has no effect on labeling of NPC1-YFP, suggesting that both drugs affect processes other than NPC1 binding to cholesterol. We also developed a procedure to label the NPC1-YFP by [ 3 H]AC in vitro and showed that cholesterol is more effective in protection against labeling than its analogs epicholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 50 publications
0
156
0
1
Order By: Relevance
“…NPC2 is a soluble glycoprotein in the lumen of the late endosomes/ lysosomes (LE/LYS) (9). Both NPC1 and NPC2 bind to cholesterol (10)(11)(12)(13)(14)(15) and may cooperate in endosomal cholesterol transport (16). Whether the Golgi is involved in LDL-CHOL transport downstream of the NPC1 compartment has not yet been demonstrated.…”
Section: Transport Of Ldl-derived Cholesterol From the Npc1 Compartmementioning
confidence: 99%
“…NPC2 is a soluble glycoprotein in the lumen of the late endosomes/ lysosomes (LE/LYS) (9). Both NPC1 and NPC2 bind to cholesterol (10)(11)(12)(13)(14)(15) and may cooperate in endosomal cholesterol transport (16). Whether the Golgi is involved in LDL-CHOL transport downstream of the NPC1 compartment has not yet been demonstrated.…”
Section: Transport Of Ldl-derived Cholesterol From the Npc1 Compartmementioning
confidence: 99%
“…Thus, it is still not known which of scenarios described above is of highest signifi cance during disease progression. Similarly, it has not been conclusively determined which of the lipids sequestered in NPC lysosomes is the primary culprit reaccumulate under NPC1 or NPC2 loss-of-function ( 21,67,68 ).…”
Section: Discussionmentioning
confidence: 99%
“…(9,10) PTCH1 is composed of N-and C-terminal domains, two large extracellular and one large intracellular loops, and 12-pass transmembrane domains, two to six of which form the putative sterol-sensing domain (SSD) considered to participate in vesicular trafficking of cholesterol and other lipids. (11,12) We and other groups have reported that more than 85% of patients with NBCCS harbor heterozygous germline PTCH1 mutations, (13)(14)(15) primarily consisting of PTCH1 protein truncations (73%) that are usually concentrated in the large extracellular and intracellular loops and in the N-terminal region. Germline missense mutations (17%) occur primarily in the transmembrane domains and especially in the SSDs.…”
Section: Introductionmentioning
confidence: 99%